The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s40748-019-0098-4
|View full text |Cite
|
Sign up to set email alerts
|

Does the safe childbirth checklist (SCC) program save newborn lives? Evidence from a realistic quasi-experimental study, Rajasthan, India

Abstract: Background The WHO Safe Childbirth Checklist (SCC) is a facility-based reminder tool focusing on essential care to improve quality of intrapartum care. We aimed to assess the impact of an intervention package using the SCC tool on facility-based stillbirths (SBs) and very early neonatal deaths (vENDs), in Rajasthan, India. Methods Within a quasi-experimental framework, districts were selected as intervention or comparison, matched by annual delivery load. The SCC tool w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 29 publications
(26 reference statements)
0
62
0
Order By: Relevance
“…This early blood pressure check ensures early identi cation and management, thus prevents deterioration to severe pre-eclampsia/eclampsia. This view is validated by the quasi-experimental study [26] done in Rajasthan, India, which observed a positive behavioural change in health care providers associated with the implementation of the SCC. The greatest difference (64%) was reported in early identi cation, management and timely referral of cases of pre-eclampsia [26].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This early blood pressure check ensures early identi cation and management, thus prevents deterioration to severe pre-eclampsia/eclampsia. This view is validated by the quasi-experimental study [26] done in Rajasthan, India, which observed a positive behavioural change in health care providers associated with the implementation of the SCC. The greatest difference (64%) was reported in early identi cation, management and timely referral of cases of pre-eclampsia [26].…”
Section: Discussionmentioning
confidence: 65%
“…This view is validated by the quasi-experimental study [26] done in Rajasthan, India, which observed a positive behavioural change in health care providers associated with the implementation of the SCC. The greatest difference (64%) was reported in early identi cation, management and timely referral of cases of pre-eclampsia [26]. Though, the Better-Birth study, a clusterrandomized, controlled trial in Uttar Pradesh, India, found no signi cant impact of the SCC intervention on maternal morbidity or mortality [27], unavailability of medications and consumables may have been responsible.…”
Section: Discussionmentioning
confidence: 65%
“…The selection of the BetterBirth intervention as a case study is both a strength and limitation of this paper. During the BetterBirth Trial, the intervention was implemented with good fidelity [18] and the Safe Childbirth Checklist has been used successfully to improve clinical practice and health outcomes in other contexts [22,[77][78][79][80][81][82]. Therefore, the absence of an effect on the primary health outcomes in the BetterBirth Trial suggests that the intervention may not have been sufficiently optimized to address the specific contextual barriers to maternal and neonatal health in Uttar Pradesh [83].…”
Section: Discussionmentioning
confidence: 99%
“…As concerns the mechanism by which this occurred, a quasi-experimental study done in Rajasthan, India from 2013 -2015 observed a positive behavioural change in health care providers associated with the implementation of the SCC. The greatest difference (64%) was reported in early identification, management and timely referral of cases of pre-eclampsia [25]. However, the Better-Birth study, a cluster-randomized, controlled trial in Uttar Pradesh, India, found no significant impact of the SCC intervention on maternal morbidity or mortality [26].…”
Section: Discussionmentioning
confidence: 99%